Quantifying wildlife conflicts with metabarcoding and traditional dietary analyses: applied to seabird predation by long-nosed fur seals - Hardy, Natasha A.; Berry, Tina E.; Bunce, Michael; Bott, Nathan J.; Figueira, Will F.; McIntosh, Rebecca R. (Frontiers in Marine Science, 2024)
Wildlife conflicts require robust quantitative data on incidence and impacts, particularly among species of conservation and cultural concern. We apply a multi-assay framework to quantify predation in a southeastern Australian scenario where complex management implications and calls for predator culling have grown despite a paucity of data on seabird predation by recovering populations of long-nosed fur seals (Arctocephalus forsteri). We apply two ecological surveillance techniques to analyze this predator’s diet – traditional morphometric (prey hard-part) and environmental DNA metabarcoding (genetic) analyses using an avian specific primer for the 12S ribosomal RNA (rRNA) gene – to provide managers with estimated predation incidence, number of seabird species impacted and inter-prey species relative importance to the predator. DNA metabarcoding identified additional seabird taxa and provided relative quantitative information where multiple prey species occur within a sample; while parallel use of both genetic and hard-part analyses revealed a greater diversity of taxa than either method alone. Using data from both assays, the estimated frequency of occurrence of predation on seabirds by long-nosed fur seals ranged from 9.1–29.3% of samples and included up to 6 detected prey species. The most common seabird prey was the culturally valued little penguin (Eudyptula minor) that occurred in 6.1–25.3% of samples, higher than previously reported from traditional morphological assays alone. We then explored DNA haplotype diversity for little penguin genetic data, as a species of conservation concern, to provide a preliminary estimate of the number of individuals consumed. Polymorphism analysis of consumed little penguin DNA identified five distinct mitochondrial haplotypes – representing a minimum of 16 individual penguins consumed across 10 fur seal scat samples (equivalent to 10.1% of samples). We recommend rapid uptake and development of cost-effective genetic techniques and broader spatiotemporal sampling of fur seal diets to further quantify predation and hotspots of concern for wildlife conflict management.